2018
DOI: 10.1101/317206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In plaque-mass spectrometry imaging’ reveals a major metabolic shift towards odd-chain fatty acid lipids induced by host-virus interactions

Abstract: Tapping into the metabolic cross-talk between a host and its virus can reveal unique strategies employed during infection. Viral infection is a dynamic process that generates an evolving metabolic landscape. Gaining a continuous view into the infection process is highly challenging and is limited by current metabolomics approaches, which typically measure the average of the entire population at various stages of infection. Here, we took a novel approach to study the metabolic basis of host-virus interactions b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In bloom-forming alga Emiliania huxleyi, unsupervised spatially aware clustering indicated a systemic metabolic shift toward lipids containing OCFA induced during viral infection . Similarly, a change in lipid metabolism is associated with disease phenotypes observed in a myriad of metabolomics studies from both plants and humans.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In bloom-forming alga Emiliania huxleyi, unsupervised spatially aware clustering indicated a systemic metabolic shift toward lipids containing OCFA induced during viral infection . Similarly, a change in lipid metabolism is associated with disease phenotypes observed in a myriad of metabolomics studies from both plants and humans.…”
Section: Resultsmentioning
confidence: 95%
“…In bloom-forming alga Emiliania huxleyi , unsupervised spatially aware clustering indicated a systemic metabolic shift toward lipids containing OCFA induced during viral infection. 31 Similarly, a change in lipid metabolism is associated with disease phenotypes observed in a myriad of metabolomics studies from both plants and humans. Jenkins et al suggested an endogenous biosynthetic pathway in human plasma that results in the ratio of pentadecanoic acid (C15:0) to heptadecanoic acid (C17:0) as 1:2 instead of the expected 2:1 as seen in dairy fat.…”
Section: Resultsmentioning
confidence: 99%
“…30 In bloom-forming alga Emiliania huxleyi, unsupervised spatially-aware clustering indicated a systemic metabolic shift towards lipids containing OCFA induced during viral infection. 31 Similarly, a change in lipid metabolism is associated with disease phenotypes observed in a myriad of metabolomics studies from both plants and humans. Jenkins et al…”
Section: Putative Assignment Of Higher Mass Featuresmentioning
confidence: 99%